PELATIHAN DAN PENGUJIAN TEST OF ENGLISH AS A FOREIGN LANGUAGE (TOEFL LIKE) DI INSTITUT MANAJEMEN WIYATA INDONESIA (IMWI) SUKABUMI - Ida Zuraida; Hendar Hendar; Atri Nadia Astarina; Heri Heryono (LPPM Universitas Bina Bangsa, 2023)
This Community Service activity aims to provide training and testing of Test of English As A Foreign Language (TOEFL Like) to students of Wiyata Indonesia Institute of Management (IMWI) Sukabumi, West Java. TOEFL is a form of English language skills competence that must be possessed by students as a requirement for trial or graduation and provision to enter the world of work. The participants of this activity are second and fourth semester students. The method of implementing this activity consists of several stages, namely the initial stage in the form of observation and filling out questionnaires to find out the background of participants, followed by an introduction to the material and practice questions to identify participants' understanding of TOEFL and the form of questions tested which include listening, structure and written expressions and reading comprehension. The next stage, students are given TOEFL simulations and multimedia interactive practice and close with the final test, which is a test based on the paper-based TOEFL test (PBT). The final stage of PKM implementation is assessment, and evaluation. The results and discussion showed that before the training, the majority of participants were not familiar with TOEFL. Less than 5% of students are familiar, but after attending the training, most participants are able to understand the material and answer the questions well. TOEFL test results show that most participants are able to achieve scores that meet the required standards, some even exceed these standards. In conclusion, this training is considered effective in providing understanding and increasing participants' knowledge in taking the TOEFL test